2021
DOI: 10.1001/jamanetworkopen.2021.32262
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cost-effectiveness of Atezolizumab Plus Cobimetinib and Vemurafenib for Treatment ofBRAF V600Variation Metastatic Melanoma

Abstract: IMPORTANCEIn the IMspire150 trial, triplet treatment with atezolizumab and vemurafenib plus cobimetinib significantly improved progression-free survival (PFS) compared with vemurafenib plus cobimetinib alone for treatment of BRAF V600 variation metastatic melanoma. However, considering high cost of this combination, it is unclear if the incremental cost is worth the additional survival benefit. OBJECTIVE To evaluate the cost-effectiveness of atezolizumab and vemurafenib plus cobimetinib vs vemurafenib plus cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The combination of MEK inhibitor and anti‐PD‐1 immunotherapy was considered as a promising option. However, the phase III clinical trial of atezolizumab plus cobimetinib in advanced melanoma failed to demonstrate superior survival over anti‐PD‐1 monotherapy 43 . Other combination strategies, such as CDK4/6 inhibitors, autophagy inhibitors, or HDAC inhibitors, are also under investigation to overcome the subsequent monotherapy resistance and to prolong the survival 44–46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of MEK inhibitor and anti‐PD‐1 immunotherapy was considered as a promising option. However, the phase III clinical trial of atezolizumab plus cobimetinib in advanced melanoma failed to demonstrate superior survival over anti‐PD‐1 monotherapy 43 . Other combination strategies, such as CDK4/6 inhibitors, autophagy inhibitors, or HDAC inhibitors, are also under investigation to overcome the subsequent monotherapy resistance and to prolong the survival 44–46 …”
Section: Discussionmentioning
confidence: 99%
“…However, the phase III clinical trial of atezolizumab plus cobimetinib in advanced melanoma failed to demonstrate superior survival over anti-PD-1 monotherapy. 43 Other combination strategies, such as CDK4/6 inhibitors, autophagy inhibitors, or HDAC inhibitors, are also under investigation to overcome the subsequent monotherapy resistance and to prolong the survival. [44][45][46] Another interesting result in our study is that patients with KIT mutations also showed no survival benefit from anti-PD-1 adjuvant therapy than IFN/OBS.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness was evaluated using a partitioned survival model derived from the NCT02253459 trial data ( Partitioned survival model, 2016 ). This model is routinely employed to assess the financial and efficacy outcomes in metastatic oncology research ( Insinga et al, 2018 ; Chouaid et al, 2019 ; Loong et al, 2020 ; Cai C. et al, 2021 ). It delineates three distinct health states ( Figure 1 ): the progression-free state (from patient entry until the onset of disease progression), the progressive disease (PD) state (spanning the time the patient remains alive post the initiation of disease progression), and the terminal state.…”
Section: Methodsmentioning
confidence: 99%
“…This model is frequently employed to analyze advanced tumor diagnosis and treatment clinical efficacy and health care costs. [20][21][22][23] Three mutually exclusive health states were constructed in the current study: diseasefree progression, disease progression, and the terminal stage, as depicted in Figure 1. The model operated on a 2-week (14 days) cycle over an evaluation horizon of 240 weeks, consistent with the ASTRUM-007 trial's clinical treatment timeline.…”
Section: Model Constructionmentioning
confidence: 99%